A taxonomic and quantitative study of the endoparasites of the South African fur seal Arctocephalus pusillus pusillus Schreber, with comments on their life-histories and veterinary and medical importance - Pansegrouw, H. M.(Hendrik Marthinus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1990.